Oracle-speech in ancient Israel and divination in (Southern) African: a comparative study - Masoga, Mogomme A. (Journal for semitics, 2018)
This study compares African divination and oracle speech to prophetic oracle speech in ancient Israel. It is generally acknowledged by scholars that both African divination and prophetic oracle speech in the ancient Near Eastern (ANE) world—focusing particularly on Israel––do not confine themselves to the proclamation role, but, instead, broaden to accommodate the distinct supernatural prowess dimensions. This essay demonstrates that natural phenomena and paraphernalia––such as ditaola (divining bones), metsi (water), mmu le lefatshe (land spaces), mebala (colours), and the fauna and flora––are interrelated in an oracle-speech dialogue. The study argues for contextual and relevant perspectives of oracle speech in African divination in comparison to prophecy in ancient Israel. It is argued in this submission that oracle speeches in both Israelite prophecy and (southern) African divination share some striking similarities although some divergences can also be identified.